Alimentos volumosos na produção de leite de cabra - Ribeiro, Marcela Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
The objective of this paper was to compare dried corn plant (DCP) as a roughage (R) source for lactating goats to roughages traditionally used for feeding ruminants: alfalfa hay (AH) and coastcross hay (CCH). Twenty-one crossbred goats weighing an average of 66.48 kg were used. After reaching their lactation peak, they were distributed among seven 3 x 3 latin squares. Each experimental diet consisted of one of the roughages fed ad lib plus a commercial concentrate (C) for lactating goats, fed on a basis of 1 kg for every 2.5 kg of milk. Each group, composed by seven animals kept in a collective pen with slatted floor, stayed in each treatment for two weeks; the first week was an adaptation period, whereas milk yield measurements and milk samples were collected during the second week. Dry or as-fed matter intake was higher in AH than in DCP or CCH. No treatment effect on C intake was detected. The higher dry matter intake in AH led to higher intakes of crude protein, ether extract, minerals, nitrogen-free extract, total digestible nutrients and acid detergent fiber, both in R and in the total diet (R + C). No treatment effect was observed for either crude fiber or neutral detergent fiber intakes in R and in R+C. Milk yield and milk PB content were higher in AH than in DCP or CCH; however, milk yield corrected for 3.5% fat and body weight loss were higher in AH than in CCH, but DCP did not differ from the other two treatments. Production cost per kg of milk was lower for DCP than for AH or CCH. The results show that DCP is a valid alternative roughage for dairy goats.
Keywords: Leite de cabra; Leite - Proteinas; Milho; Alfafa; Feno; Fibra detergente neutro; Fibra bruta; Coastcross; Corn; Crude fiber; Neutral detergent fiber